Anti-inflammatory, analgesic, and antioxidant activities of Pisonia aculeata: Folk medicinal use to scientific approach. (April 2013) - Sen, Saikat; Chakraborty, Raja; Rekha, B.; Revathi, D.; Ayyanna, S. Chinna; Hemalatha, G.; Kumar Reddy, G. Ashok; Hyndavi, S.; Ikhyatha Babu, P. Jeevan; Prakash, P. Ravi; Sridhar, C.
<x xml:space="preserve">Abstract</x> Context: Pisonia aculeata leaves (Nyctagenaceae), a Folk medicinal plant used in the treatment of several inflammation, pain, and oxidative stress associated diseases. Objective: To evaluate anti-inflammatory, analgesic, and antioxidant potential of crude methanol extract of P. aculeata leaves (MEPA). Materials and methods: Analgesic and anti-inflammatory activities of MEPA (250 and 500 mg/kg) were evaluated using writhing, formalin, hot plate, tail flick, carrageenan-induced paw edema test, and membrane stabilizing activity. Free radical scavenging activity, total phenolic and flavonoid contents of MEPA were also determined using standard methods. Results: Oral administration of MEPA showed significant (p < 0.001) inhibition of paw edema, pronounced at 4 h and 5 h after carrageenan injection, and at 200 µg/mL exerts 77.67 and 38.51% protective effect against hypotonic solution and heat induced hemolysis, respectively. MEPA (250 and 500 mg/kg) produced 35.21 and 79.14% inhibition of acetic acid-induced writhing. Furthermore, MEPA (500 mg/kg) inhibited 49.19% early and 73.14% late phase of formalin-induced hypernociception. In contrast, a lower dose of MEPA did not prevent hot plate induced nociception, while in the tail immersion method, pronounced analgesic activity was observed between 1 and 4 h postdosing. The extract possesses significant in vitro antioxidant activity and a lipid peroxidation inhibition effect. Total phenolic and total flavonoid content in MEPA were 87.99 ± 0.87 mg GAE/g and 58.98 ± 0.01 mg QE/g, respectively. Discussion and conclusion: Our findings confirmed the analgesic, anti-inflammatory and antioxidant activities of Pisonia aculeata leaves. Contents of flavonoids and phenolic compounds in extract could be correlated with its observed biological activities.